Soya/alginate interactions in extrusion cooking - Oates, Christopher G, (1988)
Previous work has shown that following the inclusion of alginate high in mannuronic acid there is a reduction in the viscosity of soya melt during extrusion, this work attempts to identify the mechanism for this effect.